Application of electric fields for controlling crystallization. Issue 34 (5th August 2019) - Alexander, Lee Fiona; Radacsi, Norbert
Abstract : This highlight gives a helicopter view on the application of electric fields and discusses its potential future applications. Abstract : This highlight investigates the different aspects of electric fields controlling crystallization, focusing on strong electric fields. Application of both internal and external electric fields, as well as utilizing both alternating and direct currents (AC and DC) are discussed, with an emphasis on protein crystallization. Attention is drawn to the similarities and opposing findings within the papers published in the field to date. It has been demonstrated that the crystallization process can be significantly enhanced by the application of electric fields. Namely, electric fields can reduce the nucleation time, control the location of nucleation, increase the product yield, control the product crystal size, enhance overall crystal quality, control the crystal orientation and control the polymorphism. In addition, recent advances including the use of an electric field for separation of multicomponent mixtures, electric field-assisted crystallization in a continuous flow, and transformation of amorphous material into crystalline are discussed.